Androgen replacement in a 48, XXYY-male patient - Heuser, Isabella; Hartmann, Andreas; Oertel, Heide-Lotte (Archives of general psychiatry, 1999)
A 32-year-old man was admitted to our institute in January 1995. A 48, XXYY karyotype had been diagnosed at the age of 6 years, subsequent to delayed speech development. Because of the primary hypergonadotrophic hypogonadism common in this disorder, androgen replacement was first considered in 1988....